SISTEM PENDUKUNG KEPUTUSAN SISTEM PENDUKUNG KEPUTUSAN PENENTUAN POSISI JABATAN YANG KOSONG DENGAN METODE WEIGHT AGGREGATED SUM PRODUCT ASSESMENT (WASPAS) (Studi Kasus : PT.Tamora Agro Lestari) - Wulanda Pratiwi; Rahmad Firdaus; Januar Al Amien (Unversitas Muhammadiyah Riau, 2021)
In the process of determining the vacant position at PT. Tamora Agro Lestari is carried out according to the needs needed by the company with an uncertain time period. The appointment of the position itself depends on the respective assessment of the assistant division concerned. Currently, the assistant assessment process is done manually, in the sense of looking at discipline, performance, skills, ethics and character. Errors in assigning employee positions have a very large impact on the company because it directly affects the productivity and financial performance of the company. Therefore, it is very important to build a computerized decision-making system that can make it easier to provide employee positions that match the needs and criteria of the company. In this study using the Weight Aggregated Sum Product Assessment (WASPAS) method. Researchers conducted Black Box testing, the test was carried out by the head of the new administration to the superior for appointment. With the creation of this system, it can make it easier for company management to make choices to fill vacant positions.